Integrating Europe informal politics and institutional change - Stacey, Jeffrey (Oxford : Oxford University Press, 2010)
Stacey explains why the EU member states actively surrender policy-making power to supranational authorities. There's general antipathy toward giving up national sovereignty so why do national governments allow the creation of any new EU laws or policies whose effects they cannot keep under their general control?
Description based on print version record.
Includes bibliographical references and index.
Keywords: European Union; Self-determination, National -- European Union countries; Political planning -- European Union countries; Legislative bodies -- European Union countries -- Reform